New Trends in the Communication of Social Workers during the COVID-19 Pandemic - Loredana-Marcela TRANCĂ (Scientific Bulletin of the Politehnica University of Timişoara: Transactions on Modern Languages, 2021)
This paper presents the results of a qualitative study conducted between April and July 2020, aiming to identify the new trends in the communication process between social workers and beneficiaries, social workers and colleagues in multidisciplinary team, as well as among social workers and other specialists from public and/or private institutions in Timiş County (Romania), specific to the COVID-19 pandemic. The research method used was the semi-structured interview addressed to 23 social workers in Timiş County. The main results of the study revealed certain communication barriers during the state of emergency between social workers and other social actors with which they interacted, as well as new adaptation strategies in the communication process.